AUTHENTIC MATERIALS MANAGEMENT SYSTEM IN THE PROCESS OF ENGLISH LANGUAGE TEACHING TO FUTURE ENGINEER-TEACHERS - Zelenin, H (Problems of Engineer-Pedagogical Education, 2019)
The article aims to consider the authentic materials using in the process of English language teaching to students of engineer-teachers specialties, the concept of "authentic materials" and concept of "training and authentic materials» have been defined. The main aspects of authentic materials using and working phases with authentic materials (preparatory stage, the stage of direct work with training material (text), the discussion stage and creative stage) have been presented in this article, the exercises for each stage are proposed and the requirements for the successful use of authentic materials in the classroom have been listed. The authentic materials using of future engineer-teachers training are considered as a means of all components development of foreign language communicative competence: language, speech, social and cultural, compensatory and training components.The article provides thatselecting the authentic materials for English classes in higher engineer-pedagogical establishments require the necessarily taking into account the cross-subject links, the curriculum of student’s specialty, the teacher’s competence both to implement integrated approach and touse high-quality information sources.The implementation of authentic texts during the work on speaking topic provides fertile ground for communicative skills development of future engineerteachers, provides their activity and personal motivation in English class. The using of these texts make the training process creative and interesting for students, but on the upside, it requires specialized methodology, other than traditional, based on the training materials. In other words, the use of authentic training materials, embracing both the written and spoken word, is helping to bridge the gap between classroom knowledge and the students’ capacity to participate in real communication. Alongside this recognition of the need to develop effective skills and strategies for the real world, there has been a growing awareness of the importance of affective factors in learning, and the use of authentic texts is now considered to be one way of maintaining or increasing future engineer-teachers’ motivation for learning a foreign language.